Sikap Ibu Terhadap Pemberian Imunisasi Measles Rubella Secara Tepat Waktu Selama Pandemi Covid-19 - Oktadevi, Dianti; Sriatmi, Ayun; Kusumastuti, Wulan (Jurnal Kesehatan Andalas, 2021)
The timeliness of Measles-Rubella (MR) immunization is still low among other immunization services for infants, including at the Tempuran Health Center, Magelang Regency. Attitude is something that influences a person's actions. Objectives: To analyzed the mother's attitude towards MR immunization services on time during the covid-19 pandemic in the working area of the Tempuran Health Center, Magelang Regency. Methods: It was quantitative research with a cross-sectional approach. The research population was mothers who have babies aged 9-12 months with a sample of 100 mothers using cluster sampling technique in each village. The research instrument was a questionnaire. The data were analyzed univariately and bivariate with the Chi-square test. Results: The timeliness of MR immunization was still low. 74% of mothers were not punctual in immunizing MR to their children even though most mothers had a good attitude (65%). The Chi-square test showed a relationship between the mother's attitude and timeliness of MR immunization (p=0.004). Conclusion: The mother's attitude was not optimal because there were various problems with the mother's attitude, so it is hoped that the mother will increase knowledge, share experiences with peer groups, and if unable to attend, ask for family assistance, while health center is expected to carry out promotions, education about measles-rubella immunization and also coordinate with health office regarding vaccine stockKeywords: Â immunization, measles-rubella, timeliness